REPRESENTATION OF SOCIAL ACTORS IN THE JAKARTA POST AND TEMPO ABOUT MAKASSAR CATHEDRAL CHURCH’S SUICIDE BOMBING CASE AND PEACE JOURNALISM - Yosephine Wastu Prajnaputri (Sanata Dharma University, 2022)
Religious radicalism which leads to terrorist attacks has long been a thorn in Indonesia as a culturally rich secular country. In spite of that, present-day radical religious groups are weakened after years of spreading terrors. Their weakening is indicated especially by their shift to internet-based radicalization strategy. It opens up an opportunity for collective counterterrorism and deradicalization attempts regardless of how implicit and shrouded the strategy may be. One of ways to seize that, is the implementation of Peace Journalism principle which has been proven as successful in building peace and preventing the proliferation of violent radical ideologies. This Critical Discourse Analysis (CDA) study aims at discussing the representation of social actors in The Jakarta Post and Tempo online news about Makassar Cathedral church’s suicide bombing case and its correlation to the implementation of Peace Journalism principles.